STRATEGIC MANAGEMENT MODEL BASED ON ISLAMIC VALUES IN ISLAMIC BOARDING SCHOOL EDUCATION - Rahmatullah, Rahmatullah; Maisyarah; Mutamakin (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
This study aims to design a strategic management model integrated with Islamic values ​​in the context of Islamic boarding school education. The literature review method is used to analyze principles such as amanah, shiddiq, ihsan, musyawarah, tawazun, and hikmah which are the philosophical foundations of institutional management. The results of the study indicate that the vision and mission of Islamic boarding schools rooted in the value of tauhid are able to guide strategic planning, implementation, and evaluation consistently. This model emphasizes an adaptive organizational structure based on syura, human resource development through Islamic managerial training, and curriculum integration that balances religious and general knowledge. Information technology is also optimized for monitoring and evaluation, while external collaboration (taawun) strengthens resource support. The implementation of Islamic values ​​in budget policies and the leadership of visionary kiai are key factors in the effectiveness and sustainability of the institution. This finding is expected to be an applicable blueprint for Islamic boarding schools in improving the quality of education and competitiveness without sacrificing Islamic values. Keywords: Strategic Management; Islamic Values; Islamic Boarding Schools; Islamic Education; Institutional Management   Abstrak Penelitian ini bertujuan merancang model manajemen strategis yang terintegrasi dengan nilai-nilai Islam dalam konteks pendidikan pesantren. Metode kajian pustaka digunakan untuk menganalisis prinsip-prinsip seperti amanah, shiddiq, ihsan, musyawarah, tawazun, dan hikmah yang menjadi landasan filosofi pengelolaan lembaga. Hasil kajian menunjukkan bahwa visi-misi pesantren yang berakar pada nilai tauhid mampu memandu perencanaan, pelaksanaan, dan evaluasi strategis secara konsisten. Model ini menekankan struktur organisasi adaptif berbasis syura, pengembangan sumber daya manusia melalui pelatihan manajerial Islami, serta integrasi kurikulum yang menyeimbangkan ilmu agama dan umum. Teknologi informasi juga dioptimalkan untuk monitoring-evaluasi, sementara kolaborasi eksternal (taawun) memperkuat dukungan sumber daya. Implementasi nilai-nilai Islam dalam kebijakan anggaran dan kepemimpinan kiai yang visioner menjadi faktor kunci efektivitas dan keberlanjutan lembaga. Temuan ini diharapkan menjadi blueprint aplikatif bagi pesantren dalam meningkatkan kualitas pendidikan dan daya saing tanpa mengorbankan nilai keislaman. Kata Kunci: Manajemen Strategis; Nilai-Nilai Islam; Pesantren; Pendidikan Islam; Pengelolaan Lembaga